2012
DOI: 10.5114/bta.2012.46568
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH PAPER Homology modeling deduced tridimensional structure of Bacillus thuringiensis Cry1Ab18 toxin

Abstract: Cry1Ab18 is an δ-endotoxin produced by Bacillus thuringiensis strain. Till date the detailed mechanism of this toxin action is unclear. Therefore, solution of the three-dimensional structure of all Cry1 family members would be desirable for a comprehensive understanding of the initial mechanisms that underlie the toxicity of this type of toxin. Here, we predict a theoretical structural model of the newly reported Cry1Ab18 δ-endotoxin, using a homology modeling technique with the structure of Cry1Aa toxin molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In our study, we identified a gene encoding a delta-endotoxin CytB protein (contig 2), and hypothetical proteins that grouped in the delta-endotoxin CytB family (contigs 3 and 4). The CytB family consists of delta-endotoxin proteins, known as pore-forming toxins (PFT), which are expressed in the soil-inhabiting bacterium B. thuringiensis during sporulation and possess cytolytic and insecticidal activities against a wide range of insects (Bravo et al 2007;Kashyap et al 2012;Pardo-Lopez et al 2013). Once ingested by the host, these toxins are activated by host proteases, leading to the formation of a pore structure in the insect membrane allowing penetration of water and ions leading to cell lysis and death (Bravo et al 2007;Pigott and Ellar 2007;Soberon et al 2009).…”
Section: Carbohydrate-binding Genesmentioning
confidence: 99%
“…In our study, we identified a gene encoding a delta-endotoxin CytB protein (contig 2), and hypothetical proteins that grouped in the delta-endotoxin CytB family (contigs 3 and 4). The CytB family consists of delta-endotoxin proteins, known as pore-forming toxins (PFT), which are expressed in the soil-inhabiting bacterium B. thuringiensis during sporulation and possess cytolytic and insecticidal activities against a wide range of insects (Bravo et al 2007;Kashyap et al 2012;Pardo-Lopez et al 2013). Once ingested by the host, these toxins are activated by host proteases, leading to the formation of a pore structure in the insect membrane allowing penetration of water and ions leading to cell lysis and death (Bravo et al 2007;Pigott and Ellar 2007;Soberon et al 2009).…”
Section: Carbohydrate-binding Genesmentioning
confidence: 99%